Analysis and modeling of factor determinants of food provision at consumer market of Ukraine - O. Panukhnyk; N. Popadynets; Y. Fedotova (Global Journal of Environmental Science and Management)
The present study investigates the socio-economic nature of the issue of food provision in the consumer market of Ukraine. It is entity content and main macroeconomic functions oriented at production, sales, and consumption of food, undertaken by the state to maintain the ongoing process of social reproduction and security guaranteeing in the country. It is hypothesized that the change in income of the population, Consumer Price Index, total expenditures of households on food and agricultural production per capita have the largest influence on food provision of the consumer market in the country. Based on the system approach the authors suggest their understanding of the factor determinants grouped by certain features, which influence the condition of food provision of the consumer market in the country. Application of factor grouping method contributed to the identification of parameters that show the links of economic factors and the condition of food provision. Correlation-regression analysis allowed revealing and assessing the dependence of the level of main food products’ consumption in the country on the major groups of factor determinants. The assessment of standardized regression coefficients contributed to determining the input of each suggested factor in the condition of food provision of the consumer market. The strong interrelation between socio-economic factors and the volumes of consumption of main food groups by the Ukrainian population, in particular, vegetable and animal products, is found. The results of the conducted analysis confirm that the condition of food provision at consumer market depends on how efficient the mechanisms of macro- and microeconomic regulation of trade and food policy of Ukraine are.